They changed the world. Crick & Watson - Helfand, Lewis (Campfire heroes., 2016)
Presents biographies of James Watson and Francis Crick in graphic novel format, chronicling each man's childhood, education, and the number of professional obstacles and successes that led to the discovery of the structure of DNA.